2013
DOI: 10.1002/wrcr.20540
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of a mathematical approach to regional frequency analysis

Abstract: [1] Estimation of design quantiles of hydrometeorological variables at critical locations in river basins is necessary for hydrological applications. To arrive at reliable estimates for locations (sites) where no or limited records are available, various regional frequency analysis (RFA) procedures have been developed over the past five decades. The most widely used procedure is based on index-flood approach and L-moments. It assumes that values of scale and shape parameters of frequency distribution are ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Later, we employed three performance indexes, namely, relative bias (RB), absolute relative bias (ARB), and relative root mean square error (RRMSE), for the flood quantiles secured by PDs at the extreme events. These are defined by the following equations [40,41]:…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
“…Later, we employed three performance indexes, namely, relative bias (RB), absolute relative bias (ARB), and relative root mean square error (RRMSE), for the flood quantiles secured by PDs at the extreme events. These are defined by the following equations [40,41]:…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
“…The index‐flood approach (Dalrymple, 1960) and its variants (e.g., Basu & Srinivas, 2013, 2016; Stedinger, 1983; Sveinsson et al., 2001, 2003) are widely used for RFA. Several assumptions underlying the conventional index‐flood approach may not be valid in a real‐world scenario (Basu & Srinivas, 2013; Sveinsson et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It involves (a) identification of a group of gauged watersheds resembling watershed of the target site (in flood generating mechanism), and (b) use of pooled information (on peak flows) from the group to perform regional frequency analysis (RFA) for arriving at the desired risk estimates. The index‐flood approach (Dalrymple, 1960) and its variants (e.g., Basu & Srinivas, 2013, 2016; Stedinger, 1983; Sveinsson et al., 2001, 2003) are widely used for RFA. Several assumptions underlying the conventional index‐flood approach may not be valid in a real‐world scenario (Basu & Srinivas, 2013; Sveinsson et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The samples for flood frequency analysis can be chosen based on the annual maximum flow or the annual peak flows over some defined truncation levels. The annual maximum flow method has been widely used for flood frequency analysis in different regions [2,[7][8][9][10][11][12][13][14][15][25][26][27][28], in which the sample is defined by the maximum flow of each year of the study period. It is essential to note that the main drawbacks of relying on peaks over threshold method are the threshold selection and assuring independence criteria [27].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported to be related to the investigation of the most suitable probability distribution for flood frequency analysis in different regions worldwide [2,[7][8][9][10][11][12][13][14][15][26][27][28][29][30][31][32][33]. Ahilan et al [29] compared the family of extreme value distributions using the data from 172 gauging stations in Ireland; they reported that the Gumbel distribution outperformed the other two types of extreme value distributions (i.e., Frechet, and Weibull).…”
Section: Introductionmentioning
confidence: 99%